2018
DOI: 10.1007/s10753-018-0884-6
|View full text |Cite
|
Sign up to set email alerts
|

Lung-Resident Mesenchymal Stem Cells Promote Repair of LPS-Induced Acute Lung Injury via Regulating the Balance of Regulatory T cells and Th17 cells

Abstract: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are associated with high morbidity and mortality. Mesenchymal stem cells (MSCs) have been shown to improve ALI, and the imbalance of regulatory T cells (Tregs) and Th17 cells is associated with mortality in ALI/ARDS patients. However, whether administration of lung-resident MSC (LRMSC) improves lung injury and regulates the balance of Tregs and Th17 cells remains unknown. An ALI animal model was induced by LPS, and PBS or LRMSC were adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…MSCs also govern the specific types of immune cells that are recruited to sites of injury; biased towards the infiltration of tolerogenic cell types like regulatory T cells. In a recent study by Wang et al 56 , an improvement in LPS-induced ALI mediated by MSCs was dependent on the regulation of the balance between regulatory T cells and Th17 cells. Increased regulatory T cells were also observed in a mouse model of lung contusion following IV MSC administration 57 .…”
Section: Rationale For Msc Therapy To Manage Covid-19 Mediated Acute mentioning
confidence: 96%
“…MSCs also govern the specific types of immune cells that are recruited to sites of injury; biased towards the infiltration of tolerogenic cell types like regulatory T cells. In a recent study by Wang et al 56 , an improvement in LPS-induced ALI mediated by MSCs was dependent on the regulation of the balance between regulatory T cells and Th17 cells. Increased regulatory T cells were also observed in a mouse model of lung contusion following IV MSC administration 57 .…”
Section: Rationale For Msc Therapy To Manage Covid-19 Mediated Acute mentioning
confidence: 96%
“…When exposed to endotoxin or TNF-α, MSCs increased production of PGE 2 , which induced resident macrophage polarization toward the anti-inflammatory M2 phenotype and increased production of IL-10 (Németh et al 2009). In this context, enhanced production of IL-10 has been correlated with inhibition of rolling, adhesion, and transmigration of neutrophils (Németh et al 2009) and suppression of effector T cell neutrophil extracellular trap; NF-κB, nuclear factor-κB; o.a., oropharyngeal aspiration; PDGF, platelet-derived growth factor; TIMP, tissue inhibitor of metalloproteinase; TGF, transforming growth factor; TLR, toll-like receptor; TNF, tumor necrosis factor; TSG-6, TNF-inducible gene 6; UC, umbilical cord-derived; VEGF, vascular endothelial growth factor; VILI, ventilatorinduced lung injury proliferation (Chen et al 2014), while inducing regulatory T cell expansion (Sun et al 2011;Chao et al 2014;Wang et al 2019) and reprogramming other macrophages into the M2 phenotype (Németh et al 2009;Vasandan et al 2016). Although several studies have indicated an increase in IL-10 levels after MSC therapy, others have demonstrated a reduction in the inflammatory process with no change (Gupta et al 2012;Krasnodembskaya et al 2012) or even a decrease in IL-10 levels (Mei et al 2010;Sepúlveda et al 2014).…”
Section: Therapeutic Benefits Of Msc Therapy In Experimental Ardsmentioning
confidence: 99%
“…8). Several studies have veri ed that Treg/Th17 skewing plays a crucial role in ARDS (7,8,10,25,26). LPS, an endotoxin originating from the cell wall of gram-negative bacteria, was most used for a bacterial hyperin ammatory model of experimental ARDS (27).…”
Section: Effects Of Mir-155 Expression On Proliferation Capacity and mentioning
confidence: 99%